Pengaruh Current Ratio Dan Debt To Asset Ratio Terhadap Return On Asset Ratio Pada Pt Ramayana Lestari Sentosa Tbk Periode 2012-2024 - Indah Puji Lestari; Riski Dwi Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to determine the effect of the Current Ratio (CR) and Debt-to-Asset Ratio (DAR) on the Return on Assets (ROA) of PT Ramayana Lestari Sentosa Tbk for the period 2012–2024, both partially and simultaneously. Thus, the financial statements of PT Ramayana Lestari Sentosa Tbk were obtained. The analytical methods used in this study include descriptive statistical analysis, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, the coefficient of determination (Adjusted R²), t-tests, and F-tests using SPSS Version 27. The results of this study indicate that, when analyzed individually, the Current Ratio and Debt-to-Asset Ratio have significance values of 0.5865 > 0.05 and 0.021 < 0.05, respectively. The calculated t-values for each are also below the critical t-value (2.228), namely -0.314 and -2.883. This indicates that the Current Ratio does not have a significant partial effect on Return on Assets, while the Debt to Asset Ratio has a significant negative effect on Return on Assets. Simultaneously, the Current Ratio and Debt-to-Asset Ratio variables influence Return on Assets with a significance level of 0.021 < 0.05. The Adjusted R-Square value is 0.448. This indicates that the Current Ratio and Debt to Asset Ratio variables together account for 44.8% of the variation in Return on Assets, while the remaining 55.2% is explained by other variables outside the research model that were not examined in this study.